The Effect of Diorama Media on Improving Thematic Learning Outcomes of Grade 2 Students of Madrasah Ibtidaiyah: Pengaruh Media Diorama Terhadap Peningkatan Hasil Belajar Tematik Siswa Kelas 2 Madrasah Ibtidaiyah - Syafila, Amalia Fitri; Rindaningsih, Ida (Indonesian Journal of Education Methods Development, 2022)
The problem raised in this study is how the influence of diorama media on improving thematic learning outcomes of class II students of MI Muhammadiyah 02 Padenganploso. This study aims to analyze how the influence and how much influence the diorama media has on student learning outcomes on theme 3 of my daily tasks sub-theme 1 of my daily tasks at home learning 1 in class II MI muhammadiyah 02 padenganploso. The research method used is a quantitative experiment in the form of a pre-experimental design with the type of one group pretest-posttest design. The sample of this research is class II MI Muhammadiyah 02 Padenganploso with a total of 17 students. The sampling technique used was purposive sampling. Data analysis using simple linear regression test with the help of spss 20 for windows. Based on the test results, it can be concluded that there is a significant effect between the use of diorama media in class II MI Muhammadiyah 02 Padenganploso on thematic learning outcomes of class II students which has been proven through the results of t arithmetic greater than the value of t table, namely tcount 3,140 > ttable 2,131 and the value sig = 0.007 < 0.05. Then h0 is rejected and ha is accepted. The level of influence is evidenced by the r-square value of 0.397 and the ngain value with an average gain of 66.8603 or 66.9% which is included in the quite effective category.